2016
DOI: 10.1016/j.ceramint.2016.08.056
|View full text |Cite
|
Sign up to set email alerts
|

The indentation thermal shock behavior of laminated ZrB2–SiC ceramics with strong interfaces

Abstract: The thermal shock behavior of laminated ZrB 2-SiC ceramics with strong interfaces has been investigated by indentation-quench method through experiments and modeling, and was compared with that of a reference monolithic ZrB 2-SiC ceramic. The residual stress formed in the layers of laminated ZrB 2-SiC ceramics was also quantified by indentation technique. Results obtained by indentation-quench tests show that the monolithic and laminated ZrB 2-SiC ceramics present a similar crack growth behavior with increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…The research results show that the thermal shock resistance of layered ceramic composites with weak interfacial bonding is greatly improved compared with bulk materials due to the remarkable increase in fracture toughness, but the fracture strength is reduced. Zhou et al [ 5 , 6 ] studied the cooling thermal shock behavior and its influencing factors of layered ZrB 2 -SiC ultra-high-temperature ceramic composites with strong interface bonding through indentation quenching experiments and found that the material has higher crack growth resistance than bulk ZrB 2 -SiC ultra-high-temperature ceramic composites during thermal shock. The effect of the geometric scale on the thermal shock performance of Al 2 O 3 /ZrO 2 multilayer ceramics was examined by Bermejo [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The research results show that the thermal shock resistance of layered ceramic composites with weak interfacial bonding is greatly improved compared with bulk materials due to the remarkable increase in fracture toughness, but the fracture strength is reduced. Zhou et al [ 5 , 6 ] studied the cooling thermal shock behavior and its influencing factors of layered ZrB 2 -SiC ultra-high-temperature ceramic composites with strong interface bonding through indentation quenching experiments and found that the material has higher crack growth resistance than bulk ZrB 2 -SiC ultra-high-temperature ceramic composites during thermal shock. The effect of the geometric scale on the thermal shock performance of Al 2 O 3 /ZrO 2 multilayer ceramics was examined by Bermejo [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this condition, large crack bridging ligaments can be formed, which stabilize crack propagation. Up to now, ceramic–ceramic, metal–ceramic, metal–metal, and metal–intermetallic systems have been designed and synthesized because of their desirable properties.…”
Section: Introductionmentioning
confidence: 99%
“…One of the high temperature or ultra-high temperature ceramic materials zirconium diboride (ZrB 2 ) because of its high melting point, strength, hardness and electrical conductivity and many other excellent performance, so its application is very extensive [1][2]. The high melting point of ZrB 2 makes it difficult to be sintered into high density material.…”
Section: Introductionmentioning
confidence: 99%